Pepper & Boo : puddle trouble - Harper, Charise Mericle (Harper, Charise Mericle. Pepper & Boo, 2021)
Boo is excited about playing in the rain, while Pepper would rather stay indoors with the Cat until Boo finds a warm coat for Pepper--or the rain stops.